Analysis of temperature processes in slidewaies taking into account a friction / I.M. Kuzyaev, V.N. Anisimov // Problems of Tribology. – 2012. – № 1. – Р. 27-40. - Кузяев, И.М.; Анисимов, В.Н. (Problems of Tribology, 2014)
A mathematical model, which allows to describe non-isothermal processes in friction bearings for working organs of various chemical and other types of equipment as a result of thermal action in mating surfaces due to friction forces is developed. Program units for reproduction of developed mathematical model with MathCad are performed.